Assessment of the Awareness and Oral Hygiene Practices among Patients with Gum and Periodontal Diseases - Korniichuk, Oleksandr; Hlazunov, Oleh; Penskyi, Kostiantyn; Hlazunov, Oleksandr; Horban, Ivanna (International Journal of Statistics in Medical Research, 2024)
The level of awareness and practice of hygiene of the average person with periodontal and periodontal tissue diseases remains low and needs to be strengthened by receiving constant information, monitoring and some training from the dentist. The aim of the research is to assess awareness and practice of oral hygiene in patients with gum and periodontal diseases. Methods: 140 people were divided into two groups: I - control group (CG), relatively healthy individuals (n=40), II - patients with gum and periodontal diseases (n=100), who were interviewed, determined the Simplified Oral Health Index (OHI-S) and periodontal index at the first visit to the dentist and 6 months later. Results: Correct responses too ralhy giene questions differed significantly between groups, with the highest meanin group I and the lowest in group II. There was no statistically significant difference between the groups in termsof frequency of brushing, duration, care products, or brushing techniques. Ingroup I, the OHI-S index corresponded to a satisfactory state of hygiene (1.53 ± 0.08) compared to the control group (0.17 ± 0.01) (Table 4), while the period on talindex corresponded to the presence of gingivitis (0.81 ± 0.03) compared to the control group (0.21 ± 0.09). Conclusions: The importance of careful attention to oral hygiene, the use of various means to reduce inflammation and bleeding gums, and the reduction of dental plaque are important parameters in the prevention of gum and periodontal diseases. Prospects: Further study of awareness and oral hygiene practice with therapy in patients who have gum and periodontal diseases is required.